CUSTOMER VALUE TOWARD PURCHASE INTENTION ON LUXURY BRAND - Supriyadi Supriyadi; Hertanto Hertanto; Muhammad Rafiq (Business and Entrepreneurial Review, 2020)
This research discusses various aspects related to Luxury Brand, where in order to research this issue, an in-depth analysis is needed because it relates to psychological factors of purchase.The research variables discussed in this research are Functionalism Values, Hedonics Value, Symbolic/Expressive Values and Financials Values of Purchases  Intentions of famous brand users.The sample used in this research amounted to 180 respondents and collected by purposive sampling method.The test is carried out by the Structurally Equations Models (SEM) method. The results of this research are (1) Functional Value has a positive influence on Purchase Intention, (2) Hedonic Value has a positive influence on Purchase Intention, (3) Symbolic / expressive Value has a positive influence on Purchase Intention, (4) Financial Value does not have a positive influence on Purchase Intention. The implications obtained in this researchcan provide input for future brand development, especially for Luxury Brands.